Health professionals' perceptions of the psychological consequences of abortion - Baluk, Ulana; O'Neill, Patrick (American journal of community psychology, 1980)
Measures of depression, guilt, and state and trait anxiety were administered to doctors, nurses, and social workers under two conditions, self-report and role play. In the role-play condition, they were asked to complete the questions as would a woman who had undergone an abortion the previous day. Half of the subjects in each group were experienced with abortion patients, and half were inexperienced students. All three professional groups expected extreme depression, guilt, and anxiety on the part of the abortion patient, when compared with their own scores. These expectations do not match the experience reported by abortion patients in this and other studies. As previously found, nurses were more extreme in their attitudes; but this is explained in terms of their self-report data, which were also more extreme on all measures.